2007
DOI: 10.1016/j.ijrobp.2007.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Ratios in Node-Positive Breast Cancer—Long-Term Study to Clarify Discrepancy of Role of Supraclavicular and Axillary Regional Radiotherapy

Abstract: This is the first study demonstrating that for patients with > or =10 nodes examined, SART significantly improved the survival for the median and high NR groups but not for the low NR group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…Several studies have compared the nodal ratio with the ANIN in an adjuvant setting. In these studies, the nodal ratio (also described as percentage of involved nodes or ratio) had a better prognostic impact than the ANIN [11][12][13][14][15][16][17]. Truong et al [12] directly compared the nodal ratio, ANIN, and number of dissected nodes in a retrospective analysis of 543 stage I and II breast cancer patients with 1-3 positive nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have compared the nodal ratio with the ANIN in an adjuvant setting. In these studies, the nodal ratio (also described as percentage of involved nodes or ratio) had a better prognostic impact than the ANIN [11][12][13][14][15][16][17]. Truong et al [12] directly compared the nodal ratio, ANIN, and number of dissected nodes in a retrospective analysis of 543 stage I and II breast cancer patients with 1-3 positive nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the American Joint Committee on Cancer (AJCC) staging system for breast cancer is based on the number of involved axillary lymph nodes [10]. However, several studies have suggested that the percentage of involved nodes, or the nodal ratio, may be a superior indicator of axillary tumor burden given the inherent confounding of absolute number of involved nodes (ANIN) [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the causes of death were documented exactly, including seven deaths from myocardial infarction. The nodal ratio was defined as the absolute number of involved nodes/the number of nodes examined (8). The American Joint Committee on Cancer/ International Union Against Cancer staging system (5th ed.)…”
Section: Methodsmentioning
confidence: 99%
“…Troung et al [7,40,41]examined 542 patients and found a nodal ratio (NR) > 25% to be an independent prognostic factor for OS, which may therefore represent a selection criteria for PCLNI. The NR has been suggested to provide greater prognostic value than the absolute number of pN+ in the radiotherapeutic management of breast cancer [39,40,49]. In our analysis group, only 4% had a nodal ratio > 25% and, therefore, did not constitute a selection criterion.…”
Section: Periclavicular Irradiationmentioning
confidence: 87%